Values of Humanism in the Digital Society: An Anthropocentric Turn - Ilya A. Bykov; Sergey V. Kurushkin (Гуманитарный вектор)
The massive spread of digital communications has led to a transformation in communication practices. New actants appear in the network, the perception of which by various network communities is transformed under the infl uence of values shared by the participants in communication processes. Against this background, it becomes necessary to distinguish between the concepts of “communication” and “intercommunication”, representing the process of information exchange from two fundamentally different sides ‒ technocratic (information as a “measure to reduce uncertainty”) and anthropocentric (information depreciates without interaction and perception). The emergence in the digital environment of the actants imitating human behavior re-actualizes the problem we have posed, as not only the practices of interaction with these actants change but also their perception at the value level. The purpose of this article is to determine the degree of infl uence of values on the media behavior of a person when interacting with non-humans. Focus groups among different age groups of respondents (students and pensioners) revealed the attitude of representatives of different generations to chatbots and the basic principles of interaction with network actants. We found that although young people in general interact more actively with chatbots, both age groups showed a favorable attitude towards chatbots and technological progress. However, in the older age group, humanistic values manifested themselves more explicitly (the problem of a “live voice”, issues related to the emotional component of communication, and even concern for jobs that people might lose). The study also revealed the absence of the value gap between students and pensioners when interacting with non-humans. Among the respondents of both groups, there were both supporters of instrumental values and those whose perception of technology is based on terminal (fi nal) values. The conclusions made in the article open up prospects for studying the process of “humanizing” non-humans by users of various network resources and identifying the values that guide users when “humanizing” non-humans.